Comparative Study of Medium and Low Intensity Pulsed Electric Field and Its Effect on Protein and Fat of Mackerel Tuna and Shrimps - Darmawan, Arry; Qirom, Qirom; Widyasti, Arum Restu (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Pulsed electric field (PEF) is a well-known non-thermal technology used to inactivate bacteria and improve the physico-chemical properties of food products, including food products from the sea. However, the application of this technology in the seafood industry has a major challenge in terms of safety risk, namely electrical backlash. Therefore, several researchers have begun to study the reduction of PEF current intensity (ampere) to obtain the benefits of food treatment without the risk of electric backlash. A comparison of the performance of both medium and low-intensity PEF devices can be seen from conductivity, reliability, and back electricity. In addition to the device's performance, the effects obtained on seafood from medium and low-intensity PEF treatment on bacterial inactivation and chemical properties of protein and fat need attention. The results showed that low- and high-intensity PEF showed good electrical conductivity in media with various salt concentrations, namely 5%, 15%, and 20% (w/v). The reliability of the components tested were transistors, transformers, and ignition coils. In the return electricity test, PEF with low intensity has low return electricity compared to PEF with medium intensity. The testing process was carried out with the test pen spaced at a certain point from the power source. The effect of medium-intensity PEF on protein and fat was insignificant between the control and treatment samples. Comparison of the effect of medium and low-intensity PEF was highly significant at P0.05. The effect of low-intensity PEF on protein and fat is much better because it does not reduce the value of protein and fat in fish and shrimp too much. Medium-intensity PEF can be effectively treated quickly, but it takes work to apply in the home industry. Low-intensity PEF needs to be treated longer than medium-intensity PEF but tends to be safer from the risk of electrical backlash.